(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The article analyzes the interpretation of the economic concepts of «price» and «pricing» proposed by domestic and foreign scientists. Internal and external factors influencing pricing in construction companies are studied. The procedure for pricing in construction is determined, and methods for determining the estimated cost of building and installation work are considered. The purpose of the article. Consider the economic terms «price» and «pricing»; study internal and external factors influencing pricing in construction companies and determine the procedure for pricing in construction. Methods. The study’s methodological basis is regulatory acts, theoretical provisions on pricing policy, and the scientific works of famous economists on pricing in construction. The following methods were used to conduct the study: analysis of scientific literature and regulatory documents; comparative analysis of pricing policies of construction companies; expert assessment method; and economic and statistical analysis of factors influencing pricing. Results. The study analyzed regulatory acts and scientific works on the economic content of «price» and «pricing» concepts. It was found that pricing in construction organizations depends on a complex of internal and external factors, particularly the cost of materials, labor resources, regulatory and legal regulation, and market conditions. The main methods for determining the estimated cost of construction and installation works were analyzed. It was determined that an effective pricing policy of construction companies requires a flexible approach to pricing, considering changes in legislation, the level of competition and demand in the construction services market. Conclusions. In modern conditions, construction organizations face several challenges: economic instability, rising costs of materials, increased competition, and changes in state regulation. At the same time, the prospects for the development of the industry are associated with the introduction of digital technologies, ecological construction and new financial models. Research into factors influencing pricing in construction companies allows us to understand which elements have the most significant impact on the final cost of construction, help to assess the current situation on the market, and allow to find ways to reduce costs, in particular through the use of new technologies or alternative materials; make it possible to predict the impact of inflation, changes in legislation; help construction companies develop an effective pricing strategy that will attract more customers and win tenders. The pricing mechanism in construction is based on state building codes, an estimated calculation of the cost of a construction object.